Promoting equitable classroom practices in higher education : approaches beyond curriculum - Hallman, Heidi L., 1976-; Mendoza, Valerie (Transforming teaching and learning in higher education (Charlotte, N.C.), 2024)
"The current interest in diversity, equity, inclusion, and belonging (DEIB) in higher education emerges from a reality that higher education now serves an increasing diversity of college students. An increasingly diverse student body brings to campuses various backgrounds, linguistic variations, political and religious affiliations, and sexual orientations; therefore, colleges and universities have been prompted to select content, assessment measures, and instructional strategies to not only welcome and support diversity, but to also position students' diverse backgrounds as assets in the classrooms. This edited volume seeks to put theory into practice by inviting contributions by scholars who aim to transform the higher education classroom through equitable classroom practices premised on culturally sustaining pedagogy. Contributors to the edited volume are faculty in higher education who depict change in instruction that fosters a more inclusive and equitable learning environment. Seeking to create an understanding of how we can more fully humanize our students within historically dehumanizing institutions, we invite readers to consider equitable teaching practices through a variety of lenses. Under the canopy of access, connectedness, and belonging, this volume features initiatives that will hopefully inspire change in higher education"--